If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x-3=2-(-6x-2)
We move all terms to the left:
6x-3-(2-(-6x-2))=0
We calculate terms in parentheses: -(2-(-6x-2)), so:We get rid of parentheses
2-(-6x-2)
determiningTheFunctionDomain -(-6x-2)+2
We get rid of parentheses
6x+2+2
We add all the numbers together, and all the variables
6x+4
Back to the equation:
-(6x+4)
6x-6x-4-3=0
We add all the numbers together, and all the variables
-7!=0
There is no solution for this equation
| 2x+9x=3x+4 | | 6=r-8 | | 4=2(x=3) | | -z/7=3 | | 1/4x-16=2x-2 | | 10n=-10+8n | | 8=-9+a | | 3/20=-1/5y | | (5x+2)=43 | | x+6=-74 | | 3n+18=51 | | 5x+16=33 | | 4(x+9=56 | | .10x+2=32 | | 8x-5x2=0 | | 26=3f | | 8x+16x-9=6(4x+9) | | -3(2x-6)=6 | | 3/20=-y/5 | | 6(-5-2x)=-18 | | 6x(18)-57=2(18)+15 | | 12x=-4x2 | | 2x+4=5(x-1)-3(x-2) | | -13=2b-b- | | 6=12-3w | | 2p-6=p | | -4(2c-11)=-28 | | (x+41)=93 | | 2(6-4x)=-52 | | 100=25s | | ∠A=8x+6∠B=4x+38 | | -4b-6b=0 |